2021
DOI: 10.33899/ijvs.2021.131607.1980
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis, a zoonotic infection; A critical and updated analysis: A Review Article

Abstract: Toxoplasmosis is a parasitic illness caused by Toxoplasma gondii, an obligate intracellular protozoan. It may infect humans and pets, as well as other warm-blooded mammals. Toxoplasmosis can be silent in the general public but it can be deadly in immunocompromised patients. This neurotropic protozoan has been linked to an increased risk of behavioral changes in infected animals and mental illnesses in human beings. The detection of a biological pathogen linked to schizophrenia is critical to comprehend the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The ethical issues related to stopping screening for pregnant women, regardless of the expensive cost of testing for toxoplasma, in addition to the negative consequences of toxoplasmosis, which could be associated with increased intervention and treatment, indicate the need for antenatal screening for these two infections. 26 The most suitable alternative is to focus on prevention through early identification of cases and their risk factors and to enhance pregnant women’s awareness through health education during the first antenatal visit. 27 , 28 Screening in prenatal settings for such an infection is inevitable to avoid adverse consequences, as reported in a study conducted in Saudi Arabia, 8 which indicated that more than one million women underwent screening and about 9000 women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The ethical issues related to stopping screening for pregnant women, regardless of the expensive cost of testing for toxoplasma, in addition to the negative consequences of toxoplasmosis, which could be associated with increased intervention and treatment, indicate the need for antenatal screening for these two infections. 26 The most suitable alternative is to focus on prevention through early identification of cases and their risk factors and to enhance pregnant women’s awareness through health education during the first antenatal visit. 27 , 28 Screening in prenatal settings for such an infection is inevitable to avoid adverse consequences, as reported in a study conducted in Saudi Arabia, 8 which indicated that more than one million women underwent screening and about 9000 women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The infection causes huge economic losses. Cats can spill millions of oocysts and infection rates in cats reflect to the rate in local areas and populations [11,12]. Toxoplasma gondii is usually more prevalent, especially in moist, warm, and low-altitude regions, which is associated with longer viability of sporulated oocysts [13][14][15] The prevalence of toxoplasmosis in male and female domestic cats was higher in Asia, Europe, Africa, and Australia [16,17].…”
Section: Introductionmentioning
confidence: 99%